POOR ADHERENCE TO BLOOD PRESSURE MEASUREMENT RECOMMENDATIONS IN EUROPEAN DIALYSIS CENTERS. (June 2018) - Wuerzner, G.; Rossignol, P.; Van Der Niepen, P.; Pruijm, M.; Sarafidis, P.; Ferro, C.; Labriola, L.; Dhaun, N.; London, G.; Zoccali, C.; Burnier, M.; Halimi, J.; et al.
Abstract : Objective: Background: International Hypertension and Nephrology societies have issued recommendations on standardized blood pressure (BP) measurements in dialysis (Pantelis et al., J. Hypertens 2017;35:657–676). Whether these recommendations are followed in hemodialysis (HD) or peritoneal dialysis (PD) centers has not been investigated so far. The objective of this study was to assess adherence to BP measurement recommendations across dialysis centers. Design and method: An online questionnaire was sent to 600 members of two working groups from the ERA-EDTA (EUropean REnal and CArdiovascular Medicine) and the ESH (Hypertension and the Kidney). Besides basic demographic characteristics, the questionnaire included 16 items recommended for standardized BP measurement. The total score was calculated for each center. A t-test was used to detect differences in scores among regional or teaching centers and hemodialysis or peritoneal dialysis centers. Results: Ninety-five centers representing 92 (67%) hemodialysis center and 46 (33%) peritoneal dialysis centers, mostly from Europe (75%), responded to the questionnaire. Thirty-seven % were regional centers and 63% were teaching centers. The percentage of adherence to at least 4, 8, 12 and 16 recommendations was respectively 99 %, 93%, 51% and 4%. The mean score was 11.5 ± 2.7 out of 16 recommendations. Measurement of arm circumference and assessment of patients' condition (nervosity, tobacco, caffeine intake) before BP measurement were the two least followed recommendations (20% and 39% of centers, respectively). Notably also, in 45% of centers, assessment of BP was based on a single BP measurement. The score of adherence to BP measurement recommendations did not differ between regional (11.6 ± 2.7) and teaching centers (11.5 ± 2.6, P = 0.91). In contrast, PD centers had a higher score than HD centers (12.5 ± 2.5 vs 11.1 ± 2.7, P = 0.004). In addition, the level of adherence was higher in physicians who reported following KDIGO guidelines (11.7 ± 2.7 vs 10.3 ± 2.4, P = 0.032). Conclusions: Some standard recommendations for BP measurement are poorly followed in dialysis centers. Only a minority of centers are fully adherent to BP measurement recommendations. These results may partly explain the poor association between BP in dialysis centers and outcome.